2021
DOI: 10.3390/ma14040900
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Dependent Particle Interactions of Magnesium Aluminometasilicates as Their Performance Factor in Powder Flow and Compaction Applications

Abstract: In the pharmaceutical industry, silicates are commonly used excipients with different application possibilities. They are especially utilized as glidants in low concentrations, but they can be used in high concentrations as porous carriers and coating materials in oral solid drug delivery systems. The desirable formulations of such systems must exhibit good powder flow but also good compactibility, which brings opposing requirements on inter-particle interactions. Since magnesium aluminometasilicates (MAS) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…It has been described that Neusilin US2 is porous in nature with numerous inter and intra particle apertures exists on its surface that can contribute enormous surface area and eventually helps in greater adsorption (47). Further, the SEM images in Figure 4 also demonstrated total adsorption of PEG 4000 and RXN on the surface of Neusilin US2.…”
Section: Dscmentioning
confidence: 80%
“…It has been described that Neusilin US2 is porous in nature with numerous inter and intra particle apertures exists on its surface that can contribute enormous surface area and eventually helps in greater adsorption (47). Further, the SEM images in Figure 4 also demonstrated total adsorption of PEG 4000 and RXN on the surface of Neusilin US2.…”
Section: Dscmentioning
confidence: 80%
“…Liquisolid compacts are pills or tablets that release immediately or continuously after being swallowed, along with the addition of any necessary adjuvants for tablets or encapsulating them [2]. With a neutral pH, Neusilin® US2 is a synthetic, amorphous magnesium aluminum oximetasilicate that can be utilized for both wet granulation and direct compression of solid dosage forms [3]. Only if a maximum liquid load on the carrier material is not exceeded can one obtain an acceptable flowing and compressible liquid-solid system depending on the excipient ratio (R) of the powder substrate.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can also be used in the pharmaceutical industry as glidants in low concentrations, as well as in high concentrations as porous carriers and coating materials in oral solid drug-delivery systems. A study performed by Kominova et al [ 6 ] demonstrated the characterization of commercially available magnesium aluminometasilicates (MAS) modified by microcrystalline cellulose as a potential glidant and/or binder. It was reported that the MAS concentration and pressure applied have a significant effect on MAS behavior.…”
mentioning
confidence: 99%